1997
DOI: 10.1002/j.1551-8833.1997.tb08330.x
|View full text |Cite
|
Sign up to set email alerts
|

So Many Oocysts, So Few Outbreaks

Abstract: Prevention of waterborne disease outbreaks is a primary objective of drinking water treatment. As required by the Information Collection Rule (ICR), selected US water utilities have begun monitoring for specified chemical contaminants, Cryptosporidium, and other waterborne pathogens. When Cryptosporidium oocysts are detected during ICR monitoring, will these surveillance programs be able to estimate the risk of waterborne cryptosporidiosis? This article addresses such questions in a look at the future of surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…(1995) were selected on the basis of having no serological evidence of past infection with C. parvum . Frost et al . (1997) suggested that endemic Cryptosporidium infection, for example through surface water supplies, protects residents from illness through acquired protective immunity.…”
Section: Dose–response Curves Estimating the Risk To Humans From mentioning
confidence: 99%
“…(1995) were selected on the basis of having no serological evidence of past infection with C. parvum . Frost et al . (1997) suggested that endemic Cryptosporidium infection, for example through surface water supplies, protects residents from illness through acquired protective immunity.…”
Section: Dose–response Curves Estimating the Risk To Humans From mentioning
confidence: 99%
“…In a study of 803 Oklahoma children, 58% of adolescents (ages 14 to 21) were seropositive for Cryptosporidium parvum , indicating prior infection by the pathogen (Ford, 1999). Frost and co‐workers (1997) indicated that visitors to the United States and young children may be more susceptible to cryptosporidiosis than are mature individuals who encounter the same levels of exposure for a long period of time (and that most exposures result in asymptomatic infections rather than illness). Other studies indicated that weaker subpopulations (i.e., very young children, the elderly, pregnant women, and the immunocompromised) could die from cryptosporidiosis (Ford, 1999; Hoxie et al, 1997; Daniel, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…plain the infrequent occurrence of symptomatic illness, the absence of outbreaks in exposed populations, and a disproportionately high fraction of all outbreaks occurring among visitors to communities served by marginally treated surface-derived drinking-water supplies [3]. Because of their lower levels of protective immunity, residents of towns and cities supplied by groundwater that is periodically contaminated by either surface water or sewage may also be at high risk of illness [3].…”
mentioning
confidence: 99%
“…Because of their lower levels of protective immunity, residents of towns and cities supplied by groundwater that is periodically contaminated by either surface water or sewage may also be at high risk of illness [3].…”
mentioning
confidence: 99%